Cold spray as a novel method for development of nickel electrode coatings for hydrogen production. (5th January 2016) - Aghasibeig, Maniya; Monajatizadeh, Hossein; Bocher, Philippe; Dolatabadi, Ali; Wuthrich, Rolf; Moreau, Christian
Abstract: Cold spraying process was employed as a novel method to prepare electrocatalysts for hydrogen evolution by the water electrolysis process. Three electrode coatings were developed by cold spraying of nickel powder on aluminum substrates employing different coating parameters. The effect of the electrodes surface topography, microstructure, residual stress and surface strain on the electrocatalytic activity of the coatings was investigated using steady state polarization curves and electrochemical impedance spectroscopy. The results revealed that the largest electrocatalytic activity was obtained for the electrode with the lowest deposition efficiency that experienced the highest strain accumulation and compressive residual stress. It is expected that the large densities of dislocations along with a more favorable electronic structure of this coating caused by the peening effect encountered by the bounced-off particles were responsible for the higher activity of this electrode. Highlights: Electrode coatings for hydrogen production were deposited by cold spray. The effect of propellant gas pressure and temperature on the coatings were studied. The shot peened electrode demonstrated the highest electrocatalytic activity. High strain accumulation and residual stress caused increased catalytic activity.